2020
DOI: 10.1016/j.biomaterials.2019.119522
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis-on-Chip: Electric field modulated transdifferentiation of human mesenchymal stem cell and mouse muscle precursor cell coculture

Abstract: A number of bioengineering strategies, using biophysical stimulation, are being explored to guide the human mesenchymal stem cells (hMScs) into different lineages. In this context, we have limited understanding on the transdifferentiation of matured cells to another functional-cell type, when grown with stem cells, in a constrained cellular microenvironment under biophysical stimulation. While addressing such aspects, the present work reports the influence of the electric field (EF) stimulation on the phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 113 publications
1
32
0
Order By: Relevance
“…The mouse cells mirror the biology of human cells well in various aspects (33). Previous studies (34)(35)(36) have also demonstrated that human cells and/or their cM have protective effects in mouse and rat cells. Therefore, c2c12 cells were used in the present study.…”
Section: Introductionmentioning
confidence: 87%
“…The mouse cells mirror the biology of human cells well in various aspects (33). Previous studies (34)(35)(36) have also demonstrated that human cells and/or their cM have protective effects in mouse and rat cells. Therefore, c2c12 cells were used in the present study.…”
Section: Introductionmentioning
confidence: 87%
“…Dong et al treat NSCs with ES for 3 days at 150 mV/mm, resulting in increased achaete-scute homolog (Ascl1) expression that was further proven to regulate phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) pathway in NSCs [ 42 ]. In addition, hMSCs also showed increased levels of SOX2, nestin, β III-tubulin expression, and Ca 2+ oscillation after nine days of continuous exposure to 8 mV/mm ES for 20 h/day [ 43 ]. Taken together, these studies confirm the ES can induce cell orientation and migration, and enhance the differentiation of stem cells into neural cell lineages.…”
Section: Electrical Stimulation Enhances Stem Cell Neural Differentiationmentioning
confidence: 99%
“…Further, despite a long history of clinical trials, the mechanism linking electric stimuli and its sensing on the cell surface is still elusive. Therefore, during recent decades, the mechanism of EF (e.g., how cells sense and react to EFs) affecting cell adhesion, migration, proliferation, and differentiation has been extensively investigated in various primary cell/cell lines [ 206 , 207 , 208 , 209 , 210 , 211 ] including epithelial, mesenchymal, and neural cells [ 212 , 213 , 214 , 215 ]. Exposure of the cells to an electric current, if a certain current value threshold is exceeded, leads to cell death, while currents lower than 11 As/m 2 have shown no decrease in cell viability [ 216 ].…”
Section: Tailoring Osteoinduction With Anodic Tio 2 Nanotubesmentioning
confidence: 99%